The added benefit of an extra practice session in virtual reality on the development of presentation skills: A randomized control trial - Boetje, Josien; Ginkel, Stan (Journal of computer assisted learning, 2021)
Developing oral presentation skills is an essential objective of higher education. While previous research emphasized the importance of practice for developing oral presentation skills (OPS), it remains unclear what the optimal amount of practice is. This experimental field study examined the added benefit of an extra practice session in virtual reality (VR) on the progression of 35 graduate students in OPS, using a pre‐test post‐test design. In addition, the mediating effect of public speaking anxiety (PSA) was examined and the relation between PSA, preparation practices, perceived utility of VR and OPS was explored. Questionnaires and performance assessments were used in data collection. Results showed that participants gained benefits from practicing a third time before a virtual audience. Both anxious and non‐anxious participants progressed similarly on presentation skills and experienced the VR intervention comparably. However, the optimal number of practice presentations remains unclear and should be further investigated. Lay Description What is currently known about the subject matter Presenting is recognized as a core competence for higher educated professionals in various domains. The opportunity to practice oral presentations is considered a crucial learning environment characteristic. Modern technological solutions can offer time‐ and place‐independent practice opportunities. It remains unclear what the optimal amount of practice is for developing oral presentation skills. What this paper adds to this This study aims to provide empirical evidence for the optimal number of practice sessions on oral presentation performance. Results showed that participants gained benefits from practicing a third time before a virtual audience. Both anxious and non‐anxious participants progressed similarly on presentation skills and experienced the VR intervention comparably. The optimal number of practice presentations remains unclear and should be further investigated. The implications of study findings for practitioners Practicing several times in front of a (virtual) audience should be facilitated by educational institutions. VR can be a useful tool to facilitate repeated practice sessions, by saving both in‐class time and offering the opportunity to practice independently. VR can be used in presentation trainings for several target groups, including those with high communication‐related anxieties.